2021
DOI: 10.1007/s10151-020-02403-6
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sacral neuromodulation quadripolar tined-lead using a straight stylet: description of a surgical technique

Abstract: Background Up to 7.5% of tined-lead removals in patients having sacral neuromodulation (SNM) therapy are associated with a lead breakage. It is still unclear what adverse effects can be caused by unretrieved fragments. The aim of our study was to describe the lead removal technique we have been using for the last 2 years in our centre. Methods We retrospectively enrolled patients who had lead removal between January 2018 and January 2020 using our standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, our previous cohort study on sacral nerve stimulation using SNM lead in patients with pudendal neuralgia did not find any complications related to lead breakage during removal ( 37 ). In addition, it is possible to avoid electrode breakage by employing appropriate surgical techniques ( 38 ). Therefore, the quadripolar tined lead designed for SNM might be a safe and suitable choice for herpetic neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous cohort study on sacral nerve stimulation using SNM lead in patients with pudendal neuralgia did not find any complications related to lead breakage during removal ( 37 ). In addition, it is possible to avoid electrode breakage by employing appropriate surgical techniques ( 38 ). Therefore, the quadripolar tined lead designed for SNM might be a safe and suitable choice for herpetic neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…In those patient groups, either the sacral neuromodulation (SNM) treatment was not offered or lead removal was done in case MRI was needed. Approximately 15%-18% of SNM-implanted patients have required an explantation of the device for a variety of reasons, one being patients requiring MRI[ 14 - 17 ]. One study showed that almost 23% of total removals were attributed to patients requiring MRI[ 18 ].…”
Section: Introductionmentioning
confidence: 99%